Blood group association with SARS COVID-19 - Nafeesa Arshad 1, Saima Ashraf 2, Samavia Sana2, Roeya Rehman 2, Saqaina Anwar3, Muhammad Asif 3* (AlQalam Journal of Medical and Applied Sciences, 2020)
A pandemic disease Covid-19 spread all over the Globe. Asymptomatic, mild symptomatic or pre-symptomatic are types of corona virus. There is still no vaccine available in the market. In past many infections fever, pneumonia, HIV, are correlated with blood groups. Different blood groups have different antigens that can fight against viral disease. Blood group A is associated with Covid-19 and persons with A blood group are mostly affected than O because O blood group has anti-A-antibody but this effect is very less. In the O blood group, sugar is naturally absent that promote pathogens (a bacterium, virus, or other microorganisms that can cause disease) to attack. Behind this, different risk factors with Covid-19, some suggestion and usage of drug with some limitations are also discussed in this paper.